Financing gap for universal social protection: Global, regional and national estimates and strategies for creating fiscal space - Umberto Cattaneo; Helmut Schwarzer; Shahrashoub Razavi; Andrea Visentin (International Labour Organization (ILO), 2024)
The primary aim of the study is to provide updated estimates of the financing gap to attain universal coverage for social protection floors. This estimation encompasses 133 low- and middle-income countries, and includes five income security guarantees (for children, persons with severe disabilities, mothers of newborns, older persons and the unemployed), together with essential health care. Estimates show that, for low- and middle-income countries, the financing gap to achieve universal coverage of social protection floors is 3.3 per cent of GDP annually.1 However, for low-income countries, the financing gap is an overwhelming 52.3 per cent of their GDP annually. In 2024, for low- and middle-income countries, the additional government spending needed to achieve universal social protection represents 10.6 per cent of their annual government expenditure, or 31.6 per cent of their social protection expenditure. However, for low-income countries, building social protection floors requires the mobilization of four times their annual government expenditure or nearly 28 times their social protection expenditure.
Keywords: 330